Contemplating the Importance of Toll-like Receptors I and II Regarding Human Viral Pathogenesis - Saeed, Umar (Jundishapur J Microbiol, 2014)
BACKGROUND: Toll-like receptors (TLRs) play a major role in innate immunity, since they detect conserved pathogen-associated molecular patterns (PAMPs) on a range of microbes, including viruses, leading to innate immune activation and orchestration of the adaptive immune response. OBJECTIVES: The current study aimed to discuss earlier evidence implicating TLRs I and II in the innate immune response to viruses, in the light of more recent clinical data demonstrating that TLRs are important for anti-viral immunity in humans. MATERIALS AND METHODS: A literature search was performed via accessing research articles from PakMediNet, Pubmed and Google Scholar with key words of Toll-like receptors I and II Regarding human viral pathogenesis. The valued information on the recent scientific horizons was subjected to critical analysis. RESULTS: Comprehensive literature review illustrates important signaling pathways involved in TLR1/TLR2 mediated regulation of viral pathogenesis. TLRs mediated activation of apoptosis tends to contribute towards defense strategies utilized by innate immune response. Activation of antiviral TLR1-dependent signaling cascade would ultimately lead to activation of NF-kappa B which promotes antiviral responses via induction of specific genes. TLR1/TLR2 dimer generates intracellular signaling via IRAK4 mediated activation of IRAK1/2 which results in activation of NF-kappa B, p38 and JNK proteins in cytoplasm. NF- kappa B, p38 and JNK enter the nucleus thereby causing activation of various pro-inflammatory cytokines such as IL-1 beta, TNF-alpha, IL-6, IL-8 and IL-18. Among the chronic HCV infection, the HCV core protein induces TNF-α and IL-10 from the macrophages thereby causing reduction in release of interferon alpha. Abnormal TLR1/TLR2 signaling may contribute to the enhancement of infection-related morbidity and mortality. CONCLUSIONS: To date, a large number of viruses are proved to trigger innate immunity via TLRs, suggesting that these receptors are likely to be important in the outcome of viral infection. This suggestion is supported by the observation that many viruses have evolved mechanisms not only to evade the innate immune system, but also to subvert it for the benefit of the virus.